Dietary poly‐β‐hydroxybutyrate supplementation can effectively improve growth, digestive enzyme activities, immune‐related gene expression, disease resistance, and intestinal mucosal barrier of gibel carp, Carassius auratus gibelio. Issue 4 (10th June 2022) - Liu, Yang; Chen, Peng; Wang, Zisheng; Lv, Tingli; Li, Xiaoxia; Tian, Hongyan; Zhang, Yichan; Cang, Pingping; Chi, Shuang; Sun, Yuyu; Qiao, Guo
Abstract: Poly‐β‐hydroxybutyrate (PHB) can promote growth and enhance immunity of aquatic animals such as gibel carp, Carassius auratus gibelio . However, the optimal dietary supplementation level and feeding duration for gibel carp are still unclear. In this study, effects of various PHB supplementation levels on gibel carp growth performance, digestive enzyme activities, immune function, disease resistance, and intestinal mucosal barrier were evaluated. Six experimental diets differing in PHB levels were formulated, that is, 0% (P0 as control), 0.5% (P0.5), 1% (P1), 2% (P2), 4% (P4), and 8% (P8). Results indicated that PHB promoted fish growth performance significantly ( p  < 0.05). Compared to control group P0, the intestinal lipase, protease, and amylase activities in group P4 were significantly increased after 30 days ( p  < 0.05). Meanwhile, dietary PHB supplementation at 4% level for 30 days and 0.5% for 60 days upregulated the mRNA expression of immune‐related genes, including IL‐11, ITLN, MPO, KRT‐8, DUSP‐1, and PNP ‐5α ( p  < 0.01). Furthermore, PHB at 4% for 30 days showed positive effects on disease resistance against both viral and bacterial infections and exerted beneficial effects on maintaining epithelial mucosal barrier integrity. In conclusion, 4% PHB supplementation for 30 days or 0.5% for 60 days was recommended for gibel carp culture.